Quantitative Hedge Fund Selection - TEO, Melvyn (Institutional Knowledge at Singapore Management University, 2010)
Prior research has shown that small funds, young funds, and local funds outperform their older, larger, and distant counterparts. According to the literature, hedge fund performance is driven by fund capacity constraints, managerial incentives, and local information. I revisit these studies on hedge funds and test whether their results hold up in recent data. By doing so, I lay the foundations for a quantitative hedge fund selection framework.